Tropomyosin movement on F-actin during muscle activation explained by energy landscapes - Orzechowski, Marek; Moore, Jeffrey R.; Fischer, Stefan; Lehman, William (Archives of biochemistry and biophysics, 2014)
Muscle contraction is regulated by tropomyosin movement across the thin filament surface, which exposes or blocks myosin-binding sites on actin. Recent atomic structures of F-actin-tropomyosin have yielded the positions of tropomyosin on myosin-free and myosin-decorated actin. Here, the repositioning of α-tropomyosin between these locations on F-actin was systematically examined by optimizing the energy of the complex for a wide range of tropomyosin positions on F-actin. The resulting energy landscape provides a full-map of the F-actin surface preferred by tropomyosin, revealing a broad energy basin associated with the tropomyosin position that blocks myosin-binding. This is consistent with previously proposed low-energy oscillations of semi-rigid tropomyosin, necessary for shifting of tropomyosin following troponin-binding. In contrast, the landscape shows much less favorable energies when tropomyosin locates near its myosin-induced “open-state” position. This indicates that spontaneous movement of tropomyosin away from its energetic “ground-state” to the open-state is unlikely in absence of myosin. Instead, myosin-binding must drive tropomyosin toward the open-state to activate the thin filament. Additional energy landscapes were computed for disease-causing actin mutants that distort the topology of the actin-tropomyosin energy landscape, explaining their phenotypes. Thus, the computation of such energy landscapes offers a sensitive way to estimate the impact of mutations.
Gesehen am 21.09.2020